2019
DOI: 10.1088/1402-4896/ab2b01
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous refraction manipulation of Lamb waves using single-groove metasurfaces

Abstract: Inspired by the studies on defects in nondestructive monitoring techniques, we propose a new type of metasurface with single-groove array to manipulate Lamb waves in plate structures along arbitrary trajectories. Because of the interaction between the groove and the Lamb waves, the phase of a transmitted wave varies with the groove position. We manipulated a transmitted wave by optimizing the groove position on the metasurface and realized abnormal refraction, self-accelerating acoustic beams, and source illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For example, Xu [14] et al proposed a double-groove metasurface to cover a 0-2π phase shift of Lamb wave by digging grooves on both sides of the metasurface and arranging the grooves reasonably, and the phenomena of abnormal refraction, beam focusing and self-acceleration can be realized. Subsequently, Xu [15] et al further simplified the groove metasurface and confirmed the broadband and robustness of the single-groove metasurface through numerical simulation, which further broadened the application of the metasurface. Lin et al [16] proposed an elastic metasurface with gradient function element index (gradient folding), which can cover the phase shift of the whole 2π span by changing the gradient index common ratio between adjacent elements.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Xu [14] et al proposed a double-groove metasurface to cover a 0-2π phase shift of Lamb wave by digging grooves on both sides of the metasurface and arranging the grooves reasonably, and the phenomena of abnormal refraction, beam focusing and self-acceleration can be realized. Subsequently, Xu [15] et al further simplified the groove metasurface and confirmed the broadband and robustness of the single-groove metasurface through numerical simulation, which further broadened the application of the metasurface. Lin et al [16] proposed an elastic metasurface with gradient function element index (gradient folding), which can cover the phase shift of the whole 2π span by changing the gradient index common ratio between adjacent elements.…”
Section: Introductionmentioning
confidence: 98%
“…Usually, the former can be achieved by introducing resonant units such as pillars or columns [13][14][15][16][17][18][19][20], zigzag units [21][22][23][24][25], and blocks [26][27][28][29][30] into the structure. The latter, however, can be realized by grooves [31], notched units [32], strips [33,34] or composite strips [35,36], etc. Full phase control can also be achieved by gradient-index phononic crystals [2].…”
Section: Introductionmentioning
confidence: 99%
“…As for the non-resonant way, the phase manipulation and different functions of S0 Lamb wave were realized by changing the groove positions in the groove array structure [31]. A notched metasurface provides an innovative way to manipulate flexural waves without resonators, which supports high transmittance and multi-parameter modulation [32].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the theory of nondestructive testing, Xu et al [16] designed a metasurface with grooves on both sides of the plate to realize arbitrary regulation of Lamb waves by changing the position of grooves. Subsequently, Xu et al [17] changed the metasurface into a single-sided groove on the basis of above design. The simulation results showed that this metasurface still has a good ability to modulate Lamb waves, which further simplifies the difficulty of metasurface fabrication.…”
Section: Introductionmentioning
confidence: 99%